Development of learning materials "Chantaboon reed mat pattern of Samet Ngam community" through a participatory process: - Mulmanee, Sompong; Patjusanon, Sarita; Khotyotha, Aphissara (Asian Journal of Traditional and Innovative Arts and Textiles, 2023)
This article, Development of Learning Material in the Chanthaboon Reed Mat Pattern of the Samet Ngam Community Through a Participatory Process, aims to investigate the educational value of the Samet Ngam reed mat patterns and to create learning materials in the context of the community. It was employed by a qualitative research model to collect data and information from members of the reed mat weaving group. There were 25 people with knowledge and expertise in providing information related to reed mat patterns, obtained from purposive selection. Data and information were collected using interview guidelines. Data and information were analyzed using descriptive analysis. The research results also included that the process of creating learning material on Samet Ngam mat patterns uses a 5-step participatory process: the first step is collecting data and information to create the learning center. The second step is to create models of the reed mat patterns to serve as a database. The third step is to compile knowledge as names of patterns, characteristics, or stories that accompany those patterns and collect them into a well-accessible database. The fourth step is to display mat-pattern learning materials. And the final step is to collaborate and present the learning center. The center has a great collection of learning material from the Chanthaboon reed mat patterns. The creative media has contributed to both academic and community values.